Chemical constituents from Scutellaria hainanensis C. Y. Wu. (February 2019) - Bai, Meng; Zheng, Cai-Juan; Wu, Shou-Yuan; Chen, Guang-Ying; Song, Xiao-Ping; Han, Chang-Ri
Abstract: Seventeen compounds were obtained from the extract of the whole plant of Scutellaria hainanensis C. Y. Wu. Including eleven flavonoids (1–4 and7–13 ), two phenylpropanoids (16 and17 ), one pyridinium derivative (5 ), one ester (6 ), one phenolic derivative (14 ), and one lignanoid (15 ). Compound5 was a synthetic intermediate, newly identified as a natural product. The chemotaxonomic relationship between S. hainanensis C. Y. Wu and other species of genus Scutellaria were also discussed. As a result, the isolated glycoside compounds closely matched the ones obtained in other species of the genus.